The comparative study of electoral systems - Klingemann, Hans-Dieter (Oxford University Press, 2009)
The Comparative Study of Electoral Systems systematically deals with the question of the impact of institutions on political behaviour. It provides comparative data on the micro- and the macro-level to study electoral behaviour empirically across a broad range of institutional contexts. - ;Citizens living in presidential or parliamentary systems face different political choices as do voters casting votes in elections governed by rules of proportional representation or plurality. Political commentators seem to know how such rules influence political behaviour. They firmly believe, for example.